Efektivitas Penerapan Media Permainan Spelling Bee Untuk Meningkatkan Penguasaan Kosakata Bahasa Arab - Novi Ilmi Anggraini; Khairy Abusyairi; Muhammad Ihsanuddin Masdar (PT. Berkah Smart Academica, 2024)
Interactive and competitive learning media, such as Spelling Bee, have the potential to increase students' involvement in the learning process, which can have a positive impact on their learning outcomes, this study aims to examine the effectiveness of spelling bee learning media in improving the mastery of Arabic vocabulary of MIN 2 Samarinda students. This research is a quantitative study using a quasi-experimental approach, with a sample of 68 people consisting of 34 people (experimental class) and 34 people (control class). The data collection methods used were observation, interviews, tests consisting of pre-test and post-test and documentation. The data analysis techniques used were descriptive analysis test, normality test, homogeneity test, independent sample t-test, and N-Gain test. The results showed that the experimental group using spelling bee learning media experienced a significant increase in vocabulary mastery compared to the control group using conventional learning methods. The post-test mean value of the experimental group was 80.88, while the control group achieved a post-test mean value of 61.03 In addition, the Sig value of the t-test results of the significance value (Sig. (2 tailed)) of 0.00 because the Sig value <0.005, as the independent sample t-test test decision making that H0 is rejected and H1 is accepted. Thus, the researcher concluded that spelling bee learning media is effective in learning Arabic vocabulary.